2009
DOI: 10.1007/s00431-009-1057-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel 1p31.3p32.2 deletion involving the NFIA gene detected by array CGH in a patient with macrocephaly and hypoplasia of the corpus callosum

Abstract: Interstitial deletions or apparently balanced translocations involving bands 1p31 and 1p32 in the short arm of chromosome 1 are rarely described chromosomal imbalances. To our knowledge, there have been six cases documented to date. Five of these cases, where the NFIA gene is involved, show complex central nervous system malformations and in some cases urinary tract defects. We report another case of a microdeletion with involvement of the NFIA gene in the short arm of chromosome 1 (del(1)(p31.3p32.2)) with, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 7 publications
2
35
0
Order By: Relevance
“…20,21 There is growing evidence that haploinsufficiency for NFIA is associated with a phenotype characterized by hypoplastic or absent corpus callosum, hydrocephalus, and developmental delay, and in some patients a tethered spinal cord, Chiari type I malformation, seizures, and urinary tract anomalies. 8,[22][23][24][25] Two patients in our series had small deletions involving NFIA. Patient 99199 was noted to have a 254-kb deletion that encompasses exons 4 through 11 of NFIA (Figure 1a).…”
Section: Resultsmentioning
confidence: 96%
“…20,21 There is growing evidence that haploinsufficiency for NFIA is associated with a phenotype characterized by hypoplastic or absent corpus callosum, hydrocephalus, and developmental delay, and in some patients a tethered spinal cord, Chiari type I malformation, seizures, and urinary tract anomalies. 8,[22][23][24][25] Two patients in our series had small deletions involving NFIA. Patient 99199 was noted to have a 254-kb deletion that encompasses exons 4 through 11 of NFIA (Figure 1a).…”
Section: Resultsmentioning
confidence: 96%
“…Several studies have reported CNS malformations, including hypoplastic or absent corpus callosum, hydrocephalus, ventriculomegaly, Chiari type I malformations, and developmental delay in the chromosomal 1p32-p31 deletion syndrome (Campbell et al, 2002;Koehler et al, 2010;Chen et al, 2011;Ji et al, 2014;Rao et al, 2014). However, only a single patient with a 1p31 microdeletion had documented craniosynostosis (metopic suture closure).…”
Section: Introductionmentioning
confidence: 93%
“…Nfia mice exhibit perinatal lethality due to renal deficits, precluding analysis of this gene in the postnatal development of the brain. Interestingly, however, recent studies have reported that mutations within the human Nfia gene are correlated with neurological disorders such as a thin, hypoplastic or absent corpus callosum, and hydrocephalus or ventriculomegaly, providing evidence for the evolutionarily conserved role for this gene in brain development [32,33]. …”
Section: Nfi Genes: Key Regulators Of Nervous System Developmentmentioning
confidence: 99%